2017
DOI: 10.3390/fishes2030016
|View full text |Cite
|
Sign up to set email alerts
|

Water Oxygen Content Affects Distribution of T and B Lymphocytes in Lymphoid Tissues of Farmed Sea Bass (Dicentrarchus Labrax)

Abstract: Abstract:Intensive aquaculture systems have stimulated proper management in order to limit stressful stocking conditions and environmental impact. This should improve fish wellness and counteract adverse water characteristics such as high concentrations of carbon. The oxygen can be considered a key factor since critical conditions leading to chronic rise of blood catecholamines can depress the number and Oxygen-carrying capacity of erythrocytes. In this research, we evaluated the effects of variation in water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…It is known that WBC play a major role in the immune defensive system of fish, whereas TC are blood cells that serve mainly to form protective barriers (Magnadottir 2006). The numbers of WBC and TC may change in relation to various environmental parameters or stimuli such as infection, as well as multiple other factors, from the age of fish to species characteristics or nutritional differences (Romano et al 2017), which may explain the variations in WBC and TC values observed herein in mullets compared to goldfish, probably reflecting the different feeding habits of the two fish species under study. Notably, in a previous study it was reported that M. cephalus showed the lowest WBC and TC values with respect to two other seawater carnivores species, namely Sparus aurata and Dicentrarcus labrax (Fazio et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that WBC play a major role in the immune defensive system of fish, whereas TC are blood cells that serve mainly to form protective barriers (Magnadottir 2006). The numbers of WBC and TC may change in relation to various environmental parameters or stimuli such as infection, as well as multiple other factors, from the age of fish to species characteristics or nutritional differences (Romano et al 2017), which may explain the variations in WBC and TC values observed herein in mullets compared to goldfish, probably reflecting the different feeding habits of the two fish species under study. Notably, in a previous study it was reported that M. cephalus showed the lowest WBC and TC values with respect to two other seawater carnivores species, namely Sparus aurata and Dicentrarcus labrax (Fazio et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that the effect of chemotherapy is significantly increased immediately after hyperbaric oxygen therapy [ 42 ]. Other investigations indicated that oxygen potently affects regulatory immune responses which are dominant within the tumor loci [ 17 , 18 ]. Indeed, hypoxia promotes Treg recruitment to the site of tumor, enhances their activity in the tumor foci, and suppresses antitumor effector T cell response [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, oxygenation of tumor cells interferes with their proteomic and genomic changes and destroys them [14][15][16]. In addition, the hypoxic condition within tumors inhibits antitumor immune responses [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that high level of oxygen improved the immunocompetence in fish (Bowden, 2008; Cecchini and Saroglia, 2002). Romano et al (2017) revealed that 12 −13 mg/L oxygen increased immune response performance of sea bass ( Dicentrarchus labrax ).…”
Section: Disscussionmentioning
confidence: 99%